(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
Academic service-learning is an experiential educational strategy that integrates community service into academic courses, so learning is enhanced, and community partners receive concrete benefits. This descriptive correlation research aimed to investigate the relationship between the extent of engagement and the effectiveness of academic service community programs. Data gathered using a questionnaire and documentary analysis were treated using ranking, weighted mean, SPSS, frequency, and t- t-ratio for r. A total of 440 students (400) and lecturers (40) answered the questionnaires, and 30 participated in reliability testing of the questionnaire in the study. The extent of engagement in the academic community service program was highly engaged /seldom obtained from knowledge management, strategy implementation, motivational growth, relations and communication, extra-curricular activity development, and culture of involvement. The level of effectiveness was highly effective, obtained from a source of self-satisfaction, enhancing social responsibility, proper appropriation of resources, determination of future avenues, and responsiveness on social issues. The capabilities of engagement of knowledge management, motivational growth, extra-curricular activity development, and culture of involvement need maintenance or even enhancement. In contrast, the administrators must address the constraints on strategy implementation, relations, and communication in their engagement in academic service community programs. The capabilities of the effective source of self-satisfaction and enhancing social responsibility need maintenance or enhancement, while the constraints on the proper appropriation of resources, determination of future avenues, and responsiveness on social issues need improvements by the administrators in their effectiveness of ASCP. The validated 3-Year Strategy Plan is humbly recommended for use by the IQANIs to enhance the engagement in and effectiveness of the ASCP.